People. (Art in America, 2005)
Reports on career developments of various museum employees in the U.S. Appointment of William M. Griswold as director and president of the Minneapolis Institute of Arts; Selection of Thom Collins as the new director of the Neuberger Museum of Art in Purchase, New York; Designation of Douglas Fogle as curator at the Walker Art Center in Minneapolis.